Brainstem Chipmunk Sign: A Diagnostic Imaging Clue across All Subtypes of Alexander Disease - Armangue, Thaís; Whitehead, Matthew T.; Tonduti, Davide; Farina, Laura; Tavasoli, Ali Reza; Vossough, Arastoo; Bennett, Mariko L.; Vaia, Ylenia; Bernard, Geneviève; Salsano, Ettore; Mercimek-Andrews, Saadet; Waldman, Amy; et al. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: While classic brain MR imaging features of Alexander disease have been well-documented, lesional patterns can overlap with other leukodystrophies, especially in the early stages of the disease or in milder phenotypes. We aimed to assess the utility of a new neuroimaging sign to help increase the diagnostic specificity of Alexander disease.MATERIALS AND METHODS: A peculiar bilateral symmetric hyperintense signal on T2-weighted images affecting the medulla oblongata was identified in an index patient with type I Alexander disease. Subsequently, 5 observers performed a systematic MR imaging review for this pattern by examining 55 subjects with Alexander disease and 74 subjects with other leukodystrophies. Interobserver agreement was assessed by the κ index. Sensitivity, specificity, and receiver operating characteristic curves were determined.RESULTS: The identified pattern was present in 87% of subjects with Alexander disease and 14% of those without Alexander disease leukodystrophy (P < .001), 3 with vanishing white matter, 4 with adult polyglucosan body disease, and 3 others. It was found equally in both type I and type II Alexander disease (28/32, 88% versus 18/21, 86%; P = .851) and in subjects with unusual disease features (2/2). Sensitivity (87.3%; 95% CI, 76.0%–93.7%), specificity (86.5%; 95% CI, 76.9%–92.5%), and interobserver agreement (κ index = 0.82) were high.CONCLUSIONS: The identified pattern in the medulla oblongata, called the chipmunk sign due to its resemblance to the face of this rodent, is extremely common in subjects with Alexander disease and represents a diagnostic tool that can aid in early diagnosis, especially in subjects with otherwise atypical MR imaging findings and/or clinical features.APBDadult polyglucosan body diseaseADLDadult-onset autosomal dominant leukodystrophyAxDAlexander diseaseGFAPglial fibrillary acidic proteinIONinferior olivary nucleusIQRinterquartile rangeVWMvanishing white matter